Postural Control During Single-Leg Landing in Female Athletes After Anterior Cruciate Ligament Reconstruction - Ayane Ogura; Terumitsu Miyazaki; Hirofumi Ida; Satoshi Shibata; Masahiro Takemura (International Journal of Sports Physical Therapy)
# Background